APPLICATION OF RAILWAY SAFETY SYSTEM RADIOBLOCK - Vojtek, Martin; Matuška, Jaroslav; Kugler, Jan; Kendra, Martin (Sciendo, 2019)
This paper focus on description of railway safety system radioblock and its application. Content of the paper describes usefulness of this system on those railway lines, which have been operated according to norm about simplified supervision of railway operation. Theoretical basis of the research is proved by case study on the railway line Číčenice – Volary (Czechia). This railway line is the only railway line with this safety system nowadays. Application of these issues is evaluated from safety and technology point of view. There are some suggestions for other railway lines, which are suitable for radioblock railway safety system.
Aplikace zabezpečovacího zařízení radioblok v železniční dopravě
Keywords: railway transport; railway infrastructure; safety system; radioblock; železniční doprava; železniční infrastruktura; zabezpečovací zařízení; radioblok